2007
DOI: 10.1088/0031-9155/52/4/018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface and superficial dose for head and neck treatments using conventional or intensity-modulated techniques

Abstract: With increased use of intensity-modulated radiation therapy (IMRT) for head and neck treatment questions have arisen as to selection of an optimum treatment approach when either superficial sparing or treatment is desired. Other work has pointed out the increased superficial dose resulting from obliquity effects when multiple tangential beams are applied to head and neck treatment, as is the general case in IMRT planning. Helical tomotherapy might be expected to result in even further enhanced superficial dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 12 publications
(19 reference statements)
3
38
0
Order By: Relevance
“…They also investigated that with thermoplastic shell D Surf was 84% and 100% of the prescribed dose for parallel opposed (POP) and IMRT treatments respectively. Higgins et al [9] demonstrated that D Surf using POP, tomotherapy and IMRT were 69%, 71% and 82% respectively. Dogan and Glasgow [10] reported that D Surf with 6MV photon beam IMRT were 8% and 6% lower than those of the open field for zero and 75 0 gantry angles respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They also investigated that with thermoplastic shell D Surf was 84% and 100% of the prescribed dose for parallel opposed (POP) and IMRT treatments respectively. Higgins et al [9] demonstrated that D Surf using POP, tomotherapy and IMRT were 69%, 71% and 82% respectively. Dogan and Glasgow [10] reported that D Surf with 6MV photon beam IMRT were 8% and 6% lower than those of the open field for zero and 75 0 gantry angles respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These doses are substantially less than the predictions of the TPS (full coverage at 3 mm depth, 83% at skin surface), consistent with the documented overestimation of superficial dose by the tomotherapy TPS. [8][9][10][11][12] At a lateral displacement of 2.5 mm, the dose at 3 mm depth remained at 99.2% + 3.3% of the nondisplaced measurement (control). With 5 mm displacement, this ratio remained relatively well preserved at 92.4% + 4%.…”
Section: Resultsmentioning
confidence: 99%
“…10 While the dose at 3 mm depth was relatively unaffected by displacements less than 5 mm, it remains the case that delivered dose at superficial depths is less than that calculated by the current planning system. [9][10][11][12] If the skin is truly at risk, or it is clinically essential that structures within the buildup region for 6 MV photons receive the prescribed dose, despite increased skin toxicity, treatment with bolus or the use of a more accurate algorithm (Monte Carlo) would be required. Our results would be expected to carry over to other rotational IMRT approaches, such as intensity-modulated arc therapy, although that remains a topic of future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations